The Effect of Performance Allowances and Organizational Justice on Employee Performance Through Organizational Commitment at the Bekasi Religious Court Office - Elvira Sondang; Hary Indratjahyo; M. Irawan Noor (Indonesian Journal Economic Review (IJER), 2026)
The purpose of System Remuneration and Competence on Employee Performance With Discipline Work As Variables Mediation at the Secretariat Directorate General Agricultural Infrastructure and Facilities. Objects studied in study This is employees in the Directorate General Agricultural Infrastructure and Facilities, which are part from the Ministry of Agriculture in Indonesia. Research time September to November 2025. Study This apply approach explanatory analysis, namely purposeful approach For observe and test connection causal between variables independent and variable the proposed dependent in hypothesis. The results of System Remuneration and Competence on Employee Performance With Discipline Work As Variables Mediation at the Secretariat Directorate General Agricultural Infrastructure and Facilities ”, the following conclusions can be drawn: remuneration and competence influential positive and significant to discipline work . With Thus, the hypothesis First tested; system remuneration and competence influential positive and significant to performance employee.